Effects of herbal medicine Sijunzi decoction on rabbits after relieving intestinal obstruction - Li,L. (2017)
Intestinal obstruction leads to blockage of the movement of intestinal contents. After relieving the obstruction, patients might still suffer with compromised immune function and nutritional deficiency. This study aimed to evaluate the effects of Sijunzi decoction on restoring the immune function and nutritional status after relieving the obstruction. Experimental rabbits (2.5±0.2 kg) were randomly divided into normal control group, 2-day intestinal obstruction group, 2-day natural recovery group, 4-day natural recovery group, 2-day treated group, and 4-day treated group. Sijunzi decoction was given twice a day to the treated groups. The concentration of markers was analyzed to evaluate the immune function and nutritional status. The concentration of interleukin-2, immunoglobulins and complement components of the treated groups were significantly higher than the natural recovery group (P<0.05). The levels of CD4+ and CD4+/CD8+ increased then decreased in the treated groups. The levels of tumor necrosis factor-α and CD8+ were significantly lower than the natural recovery group. The level of total protein in the treated groups also increased then decreased after relieving the obstruction. The levels of albumin, prealbumin and insulin-like growth factor-1 were significantly higher in the treated groups than in the natural recovery group (P<0.05). Transferrin level in the treated groups was significantly higher than the obstruction group (P<0.05). Sijunzi decoction can lessen the inflammatory response and improve the nutrition absorption after relieving the obstruction.